2013
DOI: 10.1002/dta.1537
|View full text |Cite
|
Sign up to set email alerts
|

A population study of urine glycerol concentrations in elite athletes competing in North America

Abstract: Glycerol is an endogenous substance that is on the World Anti-Doping Agency's list of prohibited threshold substances due to its potential use as a plasma volume expansion agent. The WADA has set the threshold for urine glycerol, including measurement uncertainty, at 1.3 mg/mL. Glycerol in circulation largely comes from metabolism of triglycerides in order to meet energy requirements and when the renal threshold is eclipsed, glycerol is excreted into urine. In part due to ethnic differences in postprandial tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In September 2013, a glycerol threshold was set at 4.3 mg/ml [2] because the previous threshold (1.3 mg/ml) was more prone to false positives [28]. Glycerol is not expected to have an AAF and an accurate, precise and sensitive method with LC-MS was proposed for measuring it using simple urine sample preparation including a 10-fold urine dilution followed by injection into the LC coupled with high-resolution/high-accuracy MS (LC-HRMS) (dilute-and-shoot).…”
Section: Glycerolmentioning
confidence: 99%
See 1 more Smart Citation
“…In September 2013, a glycerol threshold was set at 4.3 mg/ml [2] because the previous threshold (1.3 mg/ml) was more prone to false positives [28]. Glycerol is not expected to have an AAF and an accurate, precise and sensitive method with LC-MS was proposed for measuring it using simple urine sample preparation including a 10-fold urine dilution followed by injection into the LC coupled with high-resolution/high-accuracy MS (LC-HRMS) (dilute-and-shoot).…”
Section: Glycerolmentioning
confidence: 99%
“…THCA and its glucuronide conjugate are major urinary cannabinoid metabolites and the WADA threshold for THCA is 150 ng/ml. Dilute-and-shoot method development and validation for LC-MS/MS to measure urinary THCA has been described in the literature [10][11][12] and this approach permitted more rapid sample preparation with fewer steps prior to LC-MS/ THCA 150 ng/ml 15 ng/ml 10 180 ng/ml [10][11][12][13][14][15][16][17][18][19][20][21] Salbutamol 1.0 μg/ml 0.1 μg/ml 10 1.2 μg/ml [22][23][24] Formoterol 40 ng/ml 6.0 ng/ml 15 50 ng/ml [10,[25][26][27] Glycerol 4.3 mg/ml 0.65 mg/ml 15 5.3 mg/ml [28][29][30] Morphine 1.0 μg/ml 0.15 μg/ml 15 1.3 μg/ml [31][32][33][34][35][36][37][38][39][40][41] Cathine 5.0 μg/ml 0.5 μg/ml 10 6.0 μg/ml [22] Ephedrine 10 μg/ml 0.5 μg/ml 5 11 μg/ml [42][43][44][45][46][47][48][49]…”
Section: Quantification Of Banned Substances With and Without Thresholdsmentioning
confidence: 99%
“…In order to account for potential differences in glycerol elimination originating from endogenous sources, e.g . due to ethnicity, gender, etc., 959 athletes' samples from North America were quantified concerning urinary glycerol concentrations . As a result of the findings presented therein, the above mentioned conservative threshold of 4.3 mg/mL was suggested and adopted since urinary glycerol values observed in post‐administration samples reached up to more than 60 mg/mL.…”
Section: Diuretics and Other Masking Agents And Stimulantsmentioning
confidence: 99%
“…Nevertheless, glycerol was included in the World Anti‐Doping Agency (WADA) prohibited list from January 2012 onwards, with a threshold of 1.3 mg/mL . In September 2013, the threshold was further increased to 4.3 mg/mL (Decision limit (DL) 5.3 mg/mL) because research has shown that the previous threshold might yield false positive findings . Because of the aforementioned questionable and moderate benefits of glycerol, it was not expected to have an Adverse Analytical Finding (AAF).…”
Section: Introductionmentioning
confidence: 99%